1963
DOI: 10.1037/h0047790
|View full text |Cite
|
Sign up to set email alerts
|

The effect of instructional set and need for social approval on commonality of word association responses.

Abstract: This study investigated the effect of various instructional sets (speed, relaxed time instructions, and "set popular" instructions) on commonality of word associations. Findings were generally supportive of the hypotheses: significantly more common associations were given under speed as compared to relaxed instructions, Ss were able to significantly increase their commonality scores under a set to give popular responses, and need for social approval was differentially related to commonality under relaxed but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1964
1964
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(26 citation statements)
references
References 13 publications
(11 reference statements)
1
25
0
Order By: Relevance
“…T h e instrument selected to measure social desirability was the Marlowe-Crowne Social Desirability Scale (M-C SD Scale). Horton, Marlowe, and Crowne (1963) reported that individuals scoring high on the M-C SD Scale also tended to be more conforming or other-directed, more responsive to situational demands, and more susceptible to the effects of social reinforcement than those scoring low on the Scale. Crowne and Marlowe (1964) reported an internal consistency coefficient of .88 and a test-retest reliability coefficient of .88 for the M-C SD Scale.…”
Section: Methodology the Instrumentmentioning
confidence: 98%
“…T h e instrument selected to measure social desirability was the Marlowe-Crowne Social Desirability Scale (M-C SD Scale). Horton, Marlowe, and Crowne (1963) reported that individuals scoring high on the M-C SD Scale also tended to be more conforming or other-directed, more responsive to situational demands, and more susceptible to the effects of social reinforcement than those scoring low on the Scale. Crowne and Marlowe (1964) reported an internal consistency coefficient of .88 and a test-retest reliability coefficient of .88 for the M-C SD Scale.…”
Section: Methodology the Instrumentmentioning
confidence: 98%
“…In this study, participants were asked to read a word and then write down the first word that came to their mind. Typically, word associations like "short-long" or "table-chair" are more common than word-associations like "short-fat" or "table-candle" 33 . In line with predictions derived from Uniqueness Theory, participants high in the NfU gave more novel responses compared to participants low in the NfU 32 .…”
Section: The Nfu and Creativity And Innovativenessmentioning
confidence: 99%
“…the kinds of social reinforcement which are offered in a verbal conditioning experiment, Insofar as need for approval involves behavior stereotypy along socially acceptable lines, it should relate to the number of common or popular responses given on a word association test. Horton, Marlowe & Crowne (93) find this to be true only for "relaxed" conditions;' under conditions where speed is a factor, overlearned language habits appear to overshadow any influence that personality might exert.…”
Section: Verbal Learningmentioning
confidence: 99%